(untitled) (Jurnal Manajemen Bisnis, 2026)
The expansion of financial technology (FinTech) has increased access to digital financial services, particularly among emerging digital finance users in developing urban contexts. However, while prior research has focused on initial adoption, limited attention has been given to continuance behavior. This study addresses this gap by examining the determinants of FinTech adoption and continuance among users in Makassar, Indonesia, by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) and the Expectation–Confirmation Model (ECM). Data from 200 FinTech users were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings show that Effort Expectancy and Social Influence significantly influence User Satisfaction, while Facilitating Conditions significantly affect Continuance Intention. Within the post-adoption stage, Confirmation strongly influences both Perceived Usefulness and User Satisfaction, and User Satisfaction emerges as the strongest predictor of Continuance Intention. In contrast, Performance Expectancy does not significantly affect User Satisfaction, indicating that users prioritize usability, accessibility, and social validation over performance benefits. The model explains 70.3% of the variance in Continuance Intention, demonstrating strong explanatory power. These findings emphasize the importance of user-centered design, social influence, and infrastructure support in sustaining FinTech usage, while contributing to the integration of adoption and post-adoption frameworks in emerging digital finance contexts.